Growth and yield of five prospective shallot selected accessions from true seed of shallot in lowland areas - Endang Sulistyaningsih; Retno Pangestuti; Rini Rosliani (Jurnal Ilmu Pertanian, 2020)
True seed of shallot (TSS) from open pollination crossing are in the heterogenous as a result of the heterozygous parents. This condition gives the opportunity to obtain new selected accession through the genetic variations of their seedlings. Five TSS cultivars of Biru Lancor, Pancasona, Tuk-Tuk, Lokananta, Sanren were used as planting materials to be evaluated the growth and bulb yield performance for the selection of excellent shallot selected accessions in bulb production. The 300 seeds of each cultivar were planted in the field of Faculty of Agriculture, Universitas Gadjah Mada, Banguntapan, Bantul District, Yogyakarta (100 m above sea level). All seedlings were observed for the survival rate, plant growth, and development of bulb. The results showed that the seedlings of Sanren, Lokananta, Pancasona, Tuk-Tuk, and Biru Lancor could germinate with different survival rate of 88%, 87%, 80%, 67.3% and 48%, respectively. There was a significant difference in number of leaves that effected in developing a single bulb and multi-bulb. Prospective selected accessions with high yield in lowland areas was as follows: Biru Lancor 12 plants (4%), Pancasona 20 plants (6.7%), Sanren 146 plants (48.7%), and Lokananta 25 plants (8.3%). All of the selected bulbs will be planted again for further evaluation in excellent trait of bulb aggregation (bulbs multiplication).